Export Intensity and Leverage: An Empirical Analysis of Spanish SMEs - Chalmers, David K.; Porta, Marco Della; Sensini, Luca (International Journal of Economics and Financial Issues, 2020)
The aim of this study was to contribute to the literature debate on financial behavior and corporate capital structure by focusing on two aspects. First of all, we analyzed how the intensity of exports and therefore the percentage weight of foreign sales compared to total sales affect the leverage of companies. Secondly, we have analyzed which are the most significant factors influencing the financial behavior of SMEs. The financial information for the analysis were collected from the Sabi database of Bureau Van Dijk (BVD). To select the companies to be included in the sample, we followed a methodology capable of ensuring that the sample of export oriented and non-export oriented companies was adequately represented. The overall sample size was 2000 companies. The analysis showed that export intensity has a negative and significant impact on leverage, suggesting that as exports increase, leverage decreases. In addition, profitability and business risk are negatively related to leverage, while the tangibility of the assets and growth correlates positively with leverage. Keywords: Export intensity, Leverage, profitability, Spanish SMEs JEL Classifications: G32, M16, M21 DOI: https://doi.org/10.32479/ijefi.10071